Characterization of the extracellular matrix in the chorioallantoic membrane of water buffalo (Bubalus bubalis) in early gestation. Issue 10 (6th August 2019) - Borghesi, Jéssica; da Silva Ferreira, Higor; Oliveira Favaron, Phelipe; Mario, Lara Carolina; de Almeida da Anunciação, Adriana Raquel; Oliveira, Franceliusa Delys de; Gonçalves Hayashi, Rafael; Caroprezo Morini, Adriana; Miglino, Maria Angelica
Abstract: Placenta is formed by a parenchyma rich in extracellular matrix (ECM), and this structure guarantees the proper development of the embryo and placental functioning. Recently, studies have focused on the characterization of ECM in the placenta and foetal membranes of different species. This work aimed to analyse the composition of the ECM and to quantify the types of collagens in its composition. For this, 33 chorioallantoic membranes were used at different gestational ages, which were grouped into five groups. Subsequently, haematoxylin–eosin staining, Masson trichrome and picrosirius were performed for histological analysis. Through the technique of polarized light, it was possible to quantify the total collagen present in the membranes and finally the immunohistochemical technique was performed to verify the presence of collagens and glycoproteins. It was possible to verify that the chorioallantoic membranes have, in all the gestational periods of the initial third of gestation, the same histological structures, being the most significant difference the membrane thickening that occurs gradually during the gestation. However, we notice the appearance of binucleate cells only from group II. In addition, it was verified that a gradual increase of collagen occurs until the group IV, yet from the group V begins to occur a decrease of this protein. In addition, collagen I, collagen III, fibronectin and laminin were present in all membranes. With this, we concluded that the buffalo chorioallantoic membrane presents ECM in constant remodelling at the beginning of gestation and can be used as biomaterial in works on regenerative biology.